Training in digital and didactic competences for future foreign language teachers: reflecting on the learning process - Díez-Arcón, Paz; Martín-Monje, Elena (Research in Education and Learning Innovation Archives (Online), 2024)
This study explores the evolution in the self-perceived digital and didactic competences of student-teachers completing a course on "Teaching English as a Foreign Language". The main aim of the research was to assess the impact of the integrated practice of these two competences through the completion of specific tasks. The research method chosen was mixed (quantitative and qualitative), and the self-reflection tools used were the SELFIE (Self-reflection on Effective Learning by Fostering the use of Innovative Educational Technologies) for digital competences and EPOSTL (European Portfolio for Student Teachers of Languages) for didactic competences. A total of 244 student-teachers participated in this innovative proposal during the academic year 2021-22. They had to complete collaborative tasks addressing both competences: pre-task video discussions, lesson planning, and post-task video presentations. They made use of MS Office 365 and Teams for their collaborative work. Results show that their perception of digital competence fluctuates but shows an overall improvement, while their perceived progress in didactic competence is more erratic, with a more positive result in the pre-task and in the task, but not in the post-task. This study contributes to gaining a deeper understanding of digital and didactic competence practice in teacher training, underlining the effectiveness of an integrated approach. Aquest estudi explora l’autopercepció de l’evolució en competències digitals i didàctiques de l’estudiantat-professorat que completa un curs sobre ensenyament de l’anglès com a llengua estrangera. L’objectiu principal de la investigació ha estat avaluar l’impacte de la pràctica integrada d’aquestes dues competències mitjançant la realització de tasques específiques. El mètode d’investigació triat va ser mixt (quantitatiu i qualitatiu) i les eines per a l’autoreflexió van ser el SELFIE (Self-reflection on Effective Learning by Fostering the use of Innovative Educational Technologies), per a les competències digitals, i l’EPOSTL (European Portfolio for Student Teachers of Languages), per a les competències didàctiques. En el curs 2021-22 hi van a participar 244 futurs docents, els quals van haver de dur a terme activitats col·laboratives que cobrien totes dues competències: debats sobre vídeos previs a la tasca, planificació de classes i presentacions en vídeo posteriors a la tasca. Van fer servir MS Office 365 i Teams per al seu treball col·laboratiu. Els resultats mostren que la seua percepció de la competència digital fluctua però també una millora general; mentre que el seu progrés percebut en la competència didàctica és més erràtic, amb un resultat més positiu en el debat previ i en la tasca, però no en la presentació en vídeo posterior. Aquest estudi contribueix a aprofundir en la pràctica de la competència digital i didàctica en la formació del professorat i subratlla l’eficàcia d’un enfocament integrat. Este estudio explora la autopercepción de la evolución en competencias digitales y didácticas de los estudiantes-profesores que completan un curso sobre "Enseñanza del inglés como lengua extranjera". El objetivo principal de la investigación ha sido evaluar el impacto de la práctica integrada de estas dos competencias mediante la realización de tareas específicas. El método de investigación elegido fue mixto (cuantitativo y cualitativo) y las herramientas para la autorreflexión fueron el SELFIE (Self-reflection on Effective Learning by Fostering the use of Innovative Educational Technologies) para las competencias digitales y el EPOSTL (European Portfolio for Student Teachers of Languages) para las competencias didácticas. Un total de 244 futuros docentes que participaron en el curso 2021-22, tuvieron que completar tareas colaborativas que cubrían ambas competencias: debates sobre vídeos previas a la tarea, planificación de clases y presentaciones en vídeo posteriores a la tarea. Utilizaron MS Office 365 y Teams para su trabajo colaborativo. Los resultados muestran que su percepción de la competencia digital fluctúa, pero muestra una mejora general, mientras que su progreso percibido de la competencia didáctica es más errático, con un resultado más positivo en la tarea previa y en la tarea, pero no en la tarea posterior. Este estudio contribuye a profundizar en la práctica de la competencia digital y didáctica en la formación del profesorado, subrayando la eficacia de aplicar un enfoque integrado.